Effects of water and fertilizer coupling on the physiological characteristics and growth of rabbiteye blueberry. - Xiaolan Guo (Public Library of Science (PLoS), 2021)
Understanding the impact of irrigation and fertilizer on rabbiteye blueberry (Vaccinium virgatum) physiology is necessary for its precision planting. Here, we applied varied irrigation and fertilizer under completely randomized experimental design to see its impact on the physiological characteristics and bush growth of rabbiteye blueberries. A comprehensive evaluation of the membership function was used to establish the best water-fertilizer coupling regimes. Rabbiteye blueberry enhanced the net photosynthetic rate, stomatal conductance and transpiration rate of leaf and improved its photosynthetic capacity at maximum level of irrigation water and fertilizer application (F3W4). The high fertilizer-medium water treatment (F3W3) increased leaf-soluble protein contents. The medium fertilizer-medium water treatment (F2W3, F2W2) increased leaf- soluble sugar, superoxide dismutase, and chlorophyll contents; decreased the malondialdehyde content; and enhanced leaf resistance and metabolism. It also promoted the growth of flower buds and new shoots. Combined membership function and cluster analyses revealed that the optimal water and fertilizer conditions for promoting rabbiteye blueberry plant growth were the medium fertilizer-medium water [(NH4)2SO4:Ca(H2PO4)2:K2SO4 at 59:10:20 g plant-1; 2.5 L water plant-1], medium fertilizer-medium-high water [(NH4)2SO4:Ca(H2PO4)2:K2SO4 at 59:10:20 g plant-1; 3.75 L water plant-1], and high fertilizer-medium-high water [(NH4)2SO4:Ca(H2PO4)2:K2SO4 at 118:20:40 g plant-1; 3.75 L water plant-1] treatments. The findings of this study could be used in improving the precision and efficacy of rabbiteye blueberry planting in Guizhou, China. Such an approach can increase the productivity and profitability for local fruit farmers.